2017
DOI: 10.3390/su9091527
|View full text |Cite
|
Sign up to set email alerts
|

Driving Force Analysis of the Temporal and Spatial Distribution of Flash Floods in Sichuan Province

Abstract: Flash floods are important natural disasters in China that can result in casualties and property losses. In this paper, we present a quantitative approach to examine the driving factors of the spatiotemporal distribution of flash floods based on a geographical detector. The environmental background condition (elevation, slope, etc.), precipitation, and human activity factors, as well as changes in these factors, are investigated in Sichuan Province via a driving force analysis. The results show that heavy prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 13 publications
3
22
0
1
Order By: Relevance
“…In particular, after 1980, the quantity of flash floods increased sharply (Figure 2b). The pattern is consistent with that of Sichuan Province in China [28,29]. Possible reasons include intensified human activity and increased extreme precipitation events in Fujian [63].…”
Section: Spatiotemporal Patterns Of Flash Floodssupporting
confidence: 85%
See 2 more Smart Citations
“…In particular, after 1980, the quantity of flash floods increased sharply (Figure 2b). The pattern is consistent with that of Sichuan Province in China [28,29]. Possible reasons include intensified human activity and increased extreme precipitation events in Fujian [63].…”
Section: Spatiotemporal Patterns Of Flash Floodssupporting
confidence: 85%
“…Second, a few studies have revealed the effect of human activities on flash floods, but research on the responses of flash floods to the gradual intensifying of human activity and precipitation is still rare. Finally, previous studies have detected the interaction between two driving factors [28,29], but the results did not sufficiently reflect the contribution rate of each driving factor. Therefore, research from the perspective of the interaction of multiple factors with flash floods is highly recommended.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…The catchment is located in the region that was selected for forest cover expansion under various conservation programs such as GTGP and NFCP. Moreover, it has experienced various floods in the past that have resulted in various types of disasters such as loss of human lives and economic losses [37]. Hence, the Guangyuan catchment serves as an ideal site to evaluate the impact of reforestation induced land use land cover change on flood peak discharge.…”
Section: Study Areamentioning
confidence: 99%
“…Existing research concerned with urban flooding has usually been at the basin scale [2] and usually involved: inundation analysis targeting province [3], sewer network analysis [4], and impact evaluation of flood prevention measures [5]. Recently, various models and techniques were applied to predict flooding, inundation, and its vulnerability in advanced approaches [6][7][8][9].…”
Section: Previous Studies and Selection Of Model Dimensionmentioning
confidence: 99%